Unusual localized gingival redness: a case report - Kumar, Swati; Sujir, Nanditha; Saha, Anwesha; Ahmed, Junaid; Bhushan, Prem (Frontiers in Oral Health, 2023)
Inflammation of the gingiva is one of the most common and routine findings in dental practice. These routine appearances of inflammatory gingivae can show peculiarity when associated with an underlying systemic condition or because of reactive, benign, or malignant pathologies. This case highlights minute clinical signs of the gingiva that deviate from the routine presentation and warrant further investigations. A 63-year-old woman presented with a chief complaint of severe pain in relation to the lower front teeth region for 1 month. Intraoral examination revealed a gingival lesion on the labial aspect of 41, 42, and 43, and an intraoral periapical radiograph showed mild bone loss. The lesion persisted despite oral prophylaxis, and a biopsy was advised. The final diagnosis was stage 1 gingival squamous cell carcinoma (GSCC). It is important to note that the non-descript presentation of GSCC in early stages often mimics benign traumatic or inflammatory lesions of the gingiva. Peculiar clinical features of GSCC of note include the lack of traditionally associated risk factors and localized red or ulcerative lesions with increased bleeding tendencies that do not respond to routine periodontal treatment within 2 weeks.